2015
DOI: 10.1016/j.contraception.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal contraception does not increase women’s HIV acquisition risk in Zambian discordant couples, 1994–2012

Abstract: Objective To determine the impact of hormonal contraceptive methods on risk of HIV acquisition among HIV-negative women cohabiting with HIV-positive male partners. Study design From 1994–2012, HIV discordant couples recruited from a couples’ voluntary HIV counseling and testing center in Lusaka, Zambia were followed longitudinally. HIV-negative partners were tested quarterly. This analysis is restricted to couples in which the man was HIV-positive and the woman was HIV-negative at enrollment and the man was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 22 publications
5
38
0
Order By: Relevance
“…Among 30 studies with hormonal contraceptive versus non-use of hormonal contraception comparisons, 24 included estimates specific to (or largely composed of) oral contraceptives [2124,26,27,29,39,4146,4953,55–59,61,62]. Twenty-four included estimates specific to (or largely composed of) injectables [21,2429,3948,5053,55,56,58,60,62] and three included implant-specific estimates [27,39,50,54].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 30 studies with hormonal contraceptive versus non-use of hormonal contraception comparisons, 24 included estimates specific to (or largely composed of) oral contraceptives [2124,26,27,29,39,4146,4953,55–59,61,62]. Twenty-four included estimates specific to (or largely composed of) injectables [21,2429,3948,5053,55,56,58,60,62] and three included implant-specific estimates [27,39,50,54].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four included estimates specific to (or largely composed of) injectables [21,2429,3948,5053,55,56,58,60,62] and three included implant-specific estimates [27,39,50,54]. All studies assessing DMPA assessed intramuscular DMPA, rather than the lower dose, subcutaneous formulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two higher-quality studies assessed levonorgestrel-containing contraceptive implants: adjHR for Norplant® [12, 25]: 1.6 (95% CI: 0.5-5.7) and adjHR for either Norplant® or Jadelle® [13]: 0.96 (95% CI: 0.29-1.34). Thus, while data are sparse and 95% CIs are wide, neither study suggested a statistically significant increased risk of HIV acquisition in women using levonorgestrel-containing implants.…”
Section: What Epidemiological Evidence Is Available On Levonorgestrelmentioning
confidence: 99%